Induction of Optimal Immune Responses Against Human Immunodeficiency Virus at Mucosal Portals of Entry - Vajdy, M. (Current Drug Targets - Immune, Endocrine & Metabolic Disorders, 2003)
Mucosal surfaces comprise the largest surface area of the human body and are the first line of defense against many pathogens. In fact, over 90% of common infectious disease pathogens in humans gain access to the host through mucosal membranes. A number of studies have demonstrated that mucosal immunizations induce local as well as systemic immunity. However, induction of mucosal responses by mucosal immunization is often hampered by a number of factors including degradation of vaccines at the site of delivery. Moreover, many pathogens, including the human immunodeficiency virus, HIV, primarily enter the host through a mucosal membrane after which they spread systemically. Thus, induction of optimal and protective immune responses are required at both mucosal and systemic sites. This review deals with current efforts on the induction of HIVspecific prophylactic humoral and / or cell mediated immunity in the female genital tract and rectal mucosa. The importance of the various routes of mucosal or systemic as well as combinations of mucosal and systemic immunizations through delivery of gene and protein based experimental vaccines will be reviewed. Furthermore, a summary of current and future therapeutic treatment targets will be presented.
Keywords: rectal mucosa